Photoreceptors in Chemotrophic Prokaryotes: The Case of Acinetobacter spp. Revisited - Nudel, Berta Clara (2015)
A comprehensive description of blue light using flavin (BLUF) photosensory proteins, including preferred domain architectures and the molecular mechanism of their light activation and signal generation, among chemotrophic prokaryotes is presented. Light‐regulated physiological responses in Acinetobacter spp. from environmental and clinically relevant strains are discussed. The twitching motility response in A. baylyi sp. ADP1 and the joint involvement of three of the four putative BLUF‐domain‐containing proteins in this response, in this species, is presented as an example of remarkable photoreceptor redundancy.